2010
DOI: 10.1172/jci40096
|View full text |Cite
|
Sign up to set email alerts
|

Excessive cardiac insulin signaling exacerbates systolic dysfunction induced by pressure overload in rodents

Abstract: Although many animal studies indicate insulin has cardioprotective effects, clinical studies suggest a link between insulin resistance (hyperinsulinemia) and heart failure (HF). Here we have demonstrated that excessive cardiac insulin signaling exacerbates systolic dysfunction induced by pressure overload in rodents. Chronic pressure overload induced hepatic insulin resistance and plasma insulin level elevation. In contrast, cardiac insulin signaling was upregulated by chronic pressure overload because of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(185 citation statements)
references
References 37 publications
9
173
0
3
Order By: Relevance
“…Conversely, suppression of cellular senescence in adipose tissue ameliorates inflammation and systemic metabolic dysfunction, inhibiting the progression of heart failure and the development of diabetes via modulation of insulin signaling. 15,16) In addition to WAT, other types of fat are known to be involved in regulating metabolic homeostasis. Brown adipose tissue (BAT) is highly vascular and abundant in mitochondria that are rich in uncoupling protein-1 (UCP-1), which produce heat by uncoupling the respiratory chain involved in ATP synthesis.…”
mentioning
confidence: 99%
“…Conversely, suppression of cellular senescence in adipose tissue ameliorates inflammation and systemic metabolic dysfunction, inhibiting the progression of heart failure and the development of diabetes via modulation of insulin signaling. 15,16) In addition to WAT, other types of fat are known to be involved in regulating metabolic homeostasis. Brown adipose tissue (BAT) is highly vascular and abundant in mitochondria that are rich in uncoupling protein-1 (UCP-1), which produce heat by uncoupling the respiratory chain involved in ATP synthesis.…”
mentioning
confidence: 99%
“…We previously reported that HF is associated with impaired glucose tolerance in mice and dogs, and that correction of impaired glucose tolerance with voglibose or metformin reduces HF severity (26, 27, 41). Shimizu et al (46) reported that systolic dysfunction induced by pressure overload exacerbates plasma glucose and hepatic insulin resistance via Akt and insulin signaling in rodents. In humans, chronic HF is associated with hyperinsulinemia (36,51).…”
Section: Discussionmentioning
confidence: 99%
“…Whether myostatin from the heart is also responsible for the insulin resistance or the fiber type switching (toward more slow fibers) reported to occur in heart failure was not yet examined, but both effects have been ascribed to myostatin (Fig. 4) (27,52,73,77). Interestingly, elimination of cardiac myostatin did only influence skeletal muscle mass after aortic constriction but not at baseline or after sham operation.…”
Section: Cardiac Myostatin In Health and Diseasementioning
confidence: 99%